Pressor Response to Noradrenaline in the Setting of Septic Shock: Anything New under the Sun—Dexmedetomidine, Clonidine? A Minireview - Quintin, L.; Ghignone, M.; Julien, C.; Leroy, S.; Pichot, C.; Géloën, Alain; May, C. N. (BioMed research international, 2015)
Progress over the last 50 years has led to a decline in mortality from ≈70% to ≈20% in the best series of patients with septic shock. Nevertheless, refractory septic shock still carries a mortality close to 100%. In the best series, the mortality appears related to multiple organ failure linked to comorbidities and/or an intense inflammatory response: shortening the period that the subject is exposed to circulatory instability may further lower mortality. Treatment aims at reestablishing circulation within a “central” compartment (i.e., brain, heart, and lung) but fails to reestablish a disorganized microcirculation or an adequate response to noradrenaline, the most widely used vasopressor. Indeed, steroids, nitric oxide synthase inhibitors, or donors have not achieved overwhelming acceptance in the setting of septic shock. Counterintuitively, α 2-adrenoceptor agonists were shown to reduce noradrenaline requirements in two cases of human septic shock. This has been replicated in rat and sheep models of sepsis. In addition, some data show that α 2-adrenoceptor agonists lead to an improvement in the microcirculation. Evidence-based documentation of the effects of alpha-2 agonists is needed in the setting of human septic shock.